Two new species of Syzygium (Myrtaceae) from Wawonii Island, Southeastern Sulawesi, Indonesia - Sunarti, Siti; Rugayah (Phytotaxa, 2024)
Two new species, Syzygium lampeapiense and Syzygium wawoniense, from Wawonii Island, Sulawesi, are described and illustrated. Syzygium lampeapiense is related to Syzygium comosum, while the latter is to S. ketambense. Both species are described and illustrated, and conservation assessments are provided.